2021
DOI: 10.1096/fj.202101044rrr
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A is a key positive and negative feedback regulator within interleukin‐6 trans‐signaling pathway

Abstract: Cyclophilin A (CypA) is a ubiquitously expressed protein that physiologically regulates protein folding, trafficking, and interaction. 1 It is also involved in pathological processes underlying in inflammatory diseases 2-4 and cancers. 5 Our previous studies revealed that CypA positively regulates RIG-I-mediated signaling pathway and promotes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…To confirm the right composition of rhIL‐31 or rhIL‐31RA‐hFc, the recombinant proteins were subjected to the sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) gel, and then the target bands were digested with trypsin in‐gel. The peptide samples were subjected to an EASY‐nLC 1000 interfaced via a Nanospray Flex ion source to an Orbitrap Fusion Tribrid mass spectrometer (Thermo Fisher Scientific, MA, USA) for analysis 21,22 . Mass spectra/mass spectra (MS/MS) data were processed using Mascot search engine (v.2.5.1, 2014, http://www.matrixscience.com; Matrix Science, London, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm the right composition of rhIL‐31 or rhIL‐31RA‐hFc, the recombinant proteins were subjected to the sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) gel, and then the target bands were digested with trypsin in‐gel. The peptide samples were subjected to an EASY‐nLC 1000 interfaced via a Nanospray Flex ion source to an Orbitrap Fusion Tribrid mass spectrometer (Thermo Fisher Scientific, MA, USA) for analysis 21,22 . Mass spectra/mass spectra (MS/MS) data were processed using Mascot search engine (v.2.5.1, 2014, http://www.matrixscience.com; Matrix Science, London, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Tandem MS results were searched against hIL‐31/hIL‐31RA‐hFc amino acid sequences and SWISS‐Prot/TrEMBL database (swissprot_human 20210325; 20,396 sequences; 11,364,617 residues). All the parameters were the same as previously reported 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the noninvasiveness of obtaining exosomes from body fluids, LMP1 + and LMP2A + exosomes might be promising biomarkers of ENKTCL in the clinic. Cyclophilin A (CYPA) is a member of the immunophilin family ( 109 ). Liu et al ( 110 ) demonstrated that both the serum and exosomal CYPA levels of patients with NPC were significantly higher compared with those of normal cases.…”
Section: Circulating Ebv + Exosomes Act As a Biomarker For Ebv-associated Tumor Diagnosismentioning
confidence: 99%
“…CypA positively regulates IL-6-soluble IL-6R-gp130–JAK-STAT3 signaling pathway, increasing downstream iNOS and IL-6 by inhibiting the degradation of gp130. 26 CypA promotes IL-1β maturation and secretion by enhancing K63-linked ubiquitination of pro-IL-1β in the early stages of LPS-mediated inflammation. 27 CypA increases interferon (IFN) and proinflammation cytokines production by targeting RIG-I, MAVS, and P65, and CypA deficiency leads to reduced inflammatory responses in the lungs of SeV-infected mice.…”
Section: Introductionmentioning
confidence: 99%